Laminar-specific and developmental expression of aquaporin-4 in the mouse hippocampus - Hsu, Mike S. (2011)
Mice deficient in the water channel AQP4 demonstrate increased seizure duration in response to hippocampal stimulation as well as impaired extracellular K(+) clearance. However, the expression of AQP4 in the hippocampus is not well described. In this study, we investigated i) the developmental, laminar and cell-type specificity of AQP4 expression in the hippocampus; ii) the effect of K(ir)4.1 deletion on AQP4 expression; and iii) performed Western blot and RT-PCR analyses. AQP4 immunohistochemistry on coronal sections from WT or K(ir)4.1(-/-) mice revealed a developmentally-regulated and laminar-specific pattern, with highest expression in the CA1 stratum lacunosummoleculare (SLM) and the molecular layer (ML) of the dentate gyrus (DG). AQP4 was colocalized with the glial markers GFAP and S100ß in the hippocampus, and was also ubiquitously expressed on astrocytic endfeet around blood vessels. No difference in AQP4 immunoreactivity was observed in K(ir)4.1(-/-) mice. Electrophysiological and postrecording RT-PCR analyses of individual cells revealed that AQP4 and K(ir)4.1 were co-expressed in nearly all CA1 astrocytes. In NG2 cells, AQP4 was also expressed at the transcript level. This study is the first to examine subregional AQP4 expression during development of the hippocampus. The strikingly high expression of AQP4 in the CA1 SLM and DG ML identifies these regions as potential sites of astrocytic K(+) and H(2)O regulation. These results begin to delineate the functional capabilities of hippocampal subregions and cell types for K(+) and H(2)O homeostasis, which is critical to excitability and serves as a potential target for modulation in diverse diseases.